• Accueil
• Math
• What affects the change of values of the function?...

# What affects the change of values of the function?

• Réponse publiée par: elaineeee
Subject Math

What affects the change of values of the function?

From the given values of x, substituting the numbers to each function will prove and support the answer to be stated. There are different functions to substitute the 3 values for each functions. Determining the values as (a) f(-3), (b) f(1), and (c) f(4) in each of the  following functions, the values of f(x) as x increases would be:

a. f(x) = 2xLet x= -3, f(-3) = 2(-3) , therefore ,the value of f(x) at x =-3 is -6.Let x=1, f(1) = 2(1) , therefore ,the value of f(x) at x = 1 is 2Let x=4, f(4) = 2(4) , therefore ,the value of f(x) at x = 4 is 8.

Finally,from the above result, the value of f(x) in the function f(x) = 2x increases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

b. f(x) = 2x + 1Let x= -3, f(-3) = 2(-3) + 1 , therefore ,the value of f(x) at x = -3 is -5.Let x=1, f(1) = 2(1) + 1 , therefore ,the value of f(x) at x = 1 is 3.Let x=4, f(4) = 2(4) + 1, therefore ,the value of f(x) at x = 4 is 9.

Finally,from the above result, the value of f(x) in the function f(x) = 2x + 1 increases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

c. f(x) = -3xLet x= -3, f(-3) = -3(-3) , therefore ,the value of f(x) at x = -3 is 9.Let x=1, f(1) = -3(1), therefore ,the value of f(x) at x = 1 is -3.Let x=4, f(4) = -3(4), therefore ,the value of f(x) at x = 4 is -12.

Finally,from the above result, the value of f(x) in the function f(x) = -3x decreases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

d. f(x) = -3x – 4Let x= -3, f(-3) = -3(-3) -4 , therefore ,the value of f(x) at x = -3 is 5.Let x=1, f(1) = -3(1) - 4, therefore ,the value of f(x) at x = 1 is -7.Let x=4, f(4) = -3(4) -4 , therefore ,the value of f(x) at x = 4 is -16.

Finally,from the above result, the value of f(x) in the function f(x) = -3x - 4 decreases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

e. f(x) = 2 – 3xLet x= -3, f(-3) =2-3(-3), therefore ,the value of f(x) at x = -3 is 11.Let x=1, f(1) = 2-3(1), therefore ,the value of f(x) at x = 1 is -1.Let x=4, f(4) = 2-3(4) , therefore ,the value of f(x) at x = 4 is -9.

Finally,from the above result, the value of f(x) in the function f(x) = 2 -3x decreases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

Code 8.3.2.3.3

• Réponse publiée par: danigirl12

1) a. -6, 2, 8

b. -5, 3, 9

c. 9, -3, -12

d. 5, -7, -16

e. 11, -1, -10

Step-by-step explanation:

Given Function- f(-3), f(1), f(4)

a. f(x)= 2x

f(-3)= 2(-3) = -6

f(1) = 2(1) = 2

f(4)= 2(4) = 8

b. f(x)= 2x+1

f(-3)= 2(-3)+1 = -6+1 = -5

f(1)= 2(1)+1 = 2+1 = 3

f(4)= 2(4)+1 = 8+1 = 9

c. f(x)= -3x

f(-3)= -3(-3) = 9

f(1)= -3(1) = -3

f(4)= -3(4) = -12

d. f(x)= -3x-4

f(-3)= -3(-3)-4 = 9-4 = 5

f(1)= -3(1)-4 = -3-4 = -7

f(4)= -3(4)-4 = -12-4 = -16

e. f(x)= 2-3x

f(-3)= 2-3(-3) = 2+9 = 11

f(1)= 2-3(1) = 2-3 = -1

f(4)= 2-3(4) = 2-12 = -10

Hope it helps you identify the functions. <3

• Réponse publiée par: meteor13

1.The letter "x" is often used in algebra to mean a value that is not yet known. It is called a "variable" or sometimes an "unknown". In x + 2 = 7, x is a variable, but we can work out its value if we try! A variable doesn't have to be "x", it could be "y", "w" or any letter, name or symbol.

2.

3. When the value of x increases, the value of y decreases and the graph slants downward.

4. Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4). Let x= -3, f(-3) = 2(-3) + 1 , therefore ,the value of f(x) at x = -3 is -5. Let x=1, f(1) = 2(1) + 1 , therefore ,the value of f(x) at x = 1 is 3.

5. yes

• Réponse publiée par: homersoncanceranguiu

Subject Math

What affects the change of values of the function?

From the given values of x, substituting the numbers to each function will prove and support the answer to be stated. There are different functions to substitute the 3 values for each functions. Determining the values as (a) f(-3), (b) f(1), and (c) f(4) in each of the  following functions, the values of f(x) as x increases would be:

a. f(x) = 2x

Let x= -3, f(-3) = 2(-3) , therefore ,the value of f(x) at x =-3 is -6.

Let x=1, f(1) = 2(1) , therefore ,the value of f(x) at x = 1 is 2

Let x=4, f(4) = 2(4) , therefore ,the value of f(x) at x = 4 is 8.

Finally,from the above result, the value of f(x) in the function f(x) = 2x increases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

b. f(x) = 2x + 1

Let x= -3, f(-3) = 2(-3) + 1 , therefore ,the value of f(x) at x = -3 is -5.

Let x=1, f(1) = 2(1) + 1 , therefore ,the value of f(x) at x = 1 is 3.

Let x=4, f(4) = 2(4) + 1, therefore ,the value of f(x) at x = 4 is 9.

Finally,from the above result, the value of f(x) in the function f(x) = 2x + 1 increases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

c. f(x) = -3x

Let x= -3, f(-3) = -3(-3) , therefore ,the value of f(x) at x = -3 is 9.

Let x=1, f(1) = -3(1), therefore ,the value of f(x) at x = 1 is -3.

Let x=4, f(4) = -3(4), therefore ,the value of f(x) at x = 4 is -12.

Finally,from the above result, the value of f(x) in the function f(x) = -3x decreases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

d. f(x) = -3x – 4

Let x= -3, f(-3) = -3(-3) -4 , therefore ,the value of f(x) at x = -3 is 5.

Let x=1, f(1) = -3(1) - 4, therefore ,the value of f(x) at x = 1 is -7.

Let x=4, f(4) = -3(4) -4 , therefore ,the value of f(x) at x = 4 is -16.

Finally,from the above result, the value of f(x) in the function f(x) = -3x - 4 decreases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

e. f(x) = 2 – 3x

Let x= -3, f(-3) =2-3(-3), therefore ,the value of f(x) at x = -3 is 11.

Let x=1, f(1) = 2-3(1), therefore ,the value of f(x) at x = 1 is -1.

Let x=4, f(4) = 2-3(4) , therefore ,the value of f(x) at x = 4 is -9.

Finally,from the above result, the value of f(x) in the function f(x) = 2 -3x decreases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

Step-by-step explanation:

• Réponse publiée par: JUMAIRAHtheOTAKU

kwento mo sa pagong

Step-by-step explanation:

punta ka ilog hanap ka bano tapus untog mo ulo mo

• Réponse publiée par: kuanjunjunkuan

What affects the change of values of the functions

answerFrom the given values of x, substituting the numbers to each function will prove and support the answer to be stated. There are different functions to substitute the 3 values for each functions. Determining the values as (a) f(-3), (b) f(1), and (c) f(4) in each of the  following functions, the values of f(x) as x increases would be: *a. f(x) = 2x 1. Let x= -3, f(-3) = 2(-3) , therefore ,the value of f(x) at x =-3 is -6. 2. Let x=1, f(1) = 2(1) , therefore ,the value of f(x) at x = 1 is 2 3. Let x=4, f(4) = 2(4) , therefore ,the value of f(x) at x = 4 is 8. Finally,from the above result, the value of f(x) in the function f(x) = 2x increases as x increases. Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4). *b. f(x) = 2x + 1 1. Let x= -3, f(-3) = 2(-3) + 1 , therefore ,the value of f(x) at x = -3 is -5. 2. Let x=1, f(1) = 2(1) + 1 , therefore ,the value of f(x) at x = 1 is 3. 3. Let x=4, f(4) = 2(4) + 1, therefore ,the value of f(x) at x = 4 is 9. Finally,from the above result, the value of f(x) in the function f(x) = 2x + 1 increases as x increases. Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4). *c. f(x) = -3x 1. Let x= -3, f(-3) = -3(-3) , therefore ,the value of f(x) at x = -3 is 9. 2. Let x=1, f(1) = -3(1), therefore ,the value of f(x) at x = 1 is -3. 3. Let x=4, f(4) = -3(4), therefore ,the value of f(x) at x = 4 is -12. Finally,from the above result, the value of f(x) in the function f(x) = -3x decreases as x increases. Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4). *d. f(x) = -3x – 4 1. Let x= -3, f(-3) = -3(-3) -4 , therefore ,the value of f(x) at x = -3 is 5. 2. Let x=1, f(1) = -3(1) - 4, therefore ,the value of f(x) at x = 1 is -7. 3. Let x=4, f(4) = -3(4) -4 , therefore ,the value of f(x) at x = 4 is -16. Finally,from the above result, the value of f(x) in the function f(x) = -3x - 4 decreases as x increases. Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4). *e. f(x) = 2 – 3x 1. Let x= -3, f(-3) =2-3(-3), therefore ,the value of f(x) at x = -3 is 11. 2. Let x=1, f(1) = 2-3(1), therefore ,the value of f(x) at x = 1 is -1. 3. Let x=4, f(4) = 2-3(4) , therefore ,the value of f(x) at x = 4 is -9. Finally,from the above result, the value of f(x) in the function f(x) = 2 -3x decreases as x increases. Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4). Code 8.3.2.3.3
Connaissez-vous la bonne réponse?
What affects the change of values of the function?...